HUBUNGAN PENERAPAN AKUNTANSI BERBASIS AKRUAL DAN KINERJA PEMERINTAH DI INDONESIA - Aditya Agung Satrio; Nanda Ayu Wijayanti (Journal Publicuho, 2020)
This paper studies the links between the application of accrual-based accounting and government performance. This study aims to examine the relationship between accrual accounting and government performance improvement. This study uses a quantitative approach with panel data ordered logistic regression. This study is based on 216 observation from Ministries in Indonesia from 2014 until 2016. This research contributes by providing empirical evidence with an understanding of the relationship between accrual-based accounting and performance in the Indonesian Government that has never been done before.  The results of this study prove that the implementation of accrual-based accounting is proven to improve government performance. The Indonesian government adapted government accounting standards from the International Public Sector Accounting Standards (IPSAS) published by the International Federation of Accountants (IFAC). The Indonesian government has substantially adopted these standards and not just a symbolic approach to get legitimacy in international.